Turbulence Modelling Approaches - Current State, Development Prospects, Applications 2017
DOI: 10.5772/intechopen.68361
|View full text |Cite
|
Sign up to set email alerts
|

RANS Modelling of Turbulence in Combustors

Abstract: Turbulence modelling is a major issue, affecting the precision of current numerical simulations, particularly for reacting flows. The RANS (Reynolds-averaged Navier-Stokes) modelling of turbulence is necessary in the development of advanced combustion systems in the foreseeable future. Therefore, it is important to understand advantages and limitations of these models. In this chapter, six widely used RANS turbulence models are discussed and validated against a comprehensive experimental database from a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…For the combined combustor-NGV simulations, the eddy dissipation (EDS) combustion model and discrete ordinate radiation model were used to account for species and energy source terms, and the Engineering Failure Analysis 6 realizable k-ε model was selected for turbulence momentum and scalar transfers. These models were carefully evaluated with the comprehensive database measured from a model combustor [12][13][14]. For the air-splitting over the air management elements of the combustion can, the predicted values were closely correlated to the results calculated from the semi-empirical correlations of discharge coefficients [9].…”
Section: Numerical Approach and Physical Modelsmentioning
confidence: 93%
“…For the combined combustor-NGV simulations, the eddy dissipation (EDS) combustion model and discrete ordinate radiation model were used to account for species and energy source terms, and the Engineering Failure Analysis 6 realizable k-ε model was selected for turbulence momentum and scalar transfers. These models were carefully evaluated with the comprehensive database measured from a model combustor [12][13][14]. For the air-splitting over the air management elements of the combustion can, the predicted values were closely correlated to the results calculated from the semi-empirical correlations of discharge coefficients [9].…”
Section: Numerical Approach and Physical Modelsmentioning
confidence: 93%
“…Finally, some assessments related to the numerical simulation modelling had been taken into account for a better performance in this study. For example, L. Y. Jiang [57] performed an assessment of the turbulence modeling under gas turbine conditions focusing on the turbulence models most widely used in practical engineering, which are the RANS (Reynolds-averaged Navier-Stokes) models, and concluded that all the turbulence models tested can capture the flow features or patterns. However, for the quantitative predictions of velocity, temperature and species fields, different levels of performance were revealed.…”
Section: Bibliographic Reviewmentioning
confidence: 99%
“…The methane/air mixing in the mixer was solved with ANSYS CFD Premium 16 . The realisable k-ε turbulence model and its settings were selected for this simulation, which were successfully applied to a model combustor fueled with gaseous propane 17 , and a can-annular gas turbine combustor fired by liquid jet fuel 6 .…”
Section: Numerical Simulation Of a Simple Venturi Methane/air Mixermentioning
confidence: 99%